Abstract State Machines, Alloy, B, TLA, VDM, and Z: 5th International Conference, ABZ 2016, Linz, Austria, May 23-27, 2016, Proceedings - Butler, Michael; Schewe, Klaus-Dieter; Mashkoor, Atif; Biro, Miklos (LNCS sublibrary. SL 1, Theoretical computer science and general issues, 2016)
This bookconstitutes the refereed proceedings of the 5th International Conference on AbstractState Machines, Alloy, B, TLA, VDM, and Z, ABZ 2016, held in Linz, Austria, inMay 2016. The 17 full and 15 short papers presented in this volume were carefullyreviewed and selected from 61 submissions. They record the latest researchdevelopments in state-based formal methods Abstract State Machines, Alloy, B,Circus, Event-B, TLS+, VDM and Z.